(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
The Bright Babul Blue, scientifically known as Azanus ubaldus (Stoll, 1782), has been observed for the first time in the Premtoli Social Forestation Area (N 24.387555, E 88.404246), Godagari Upazila, Rajshahi district, Bangladesh. This finding adds to our understanding of the butterfly’s distribution and underscores the importance of conserving the unique biodiversity within the Premtoli Social Forestation Area. J. Bangladesh Acad. Sci. 47(2); 277-278: December 2023